К вопросу о сущности кросс-культурного подхода в управлении персоналом предприятия (организации) - Святохо, Н.В.; Халилова, Л.А. (Культура народов Причерноморья, 2014)
В статье раскрыта сущность кросс-культурного подхода в управлении персоналом
предприятия (организации) и выявлены его особенности. Дана сравнительная характеристика
существующих подходов в управлении персоналом, а также выявлены особенности кросс-культурного
менеджмента. У статті розкрито сутність крос-культурного підходу в управлінні персоналом
підприємства (організації) та виявлено його особливості. Дана порівняльна характеристика існуючих
підходів в управлінні персоналом, а також виявлено особливості крос-культурного менеджменту. In the last 50 years, the term "personnel management" has only been used to describe the functions of
management, dedicated recruitment, development, training, rotation, safety and firing staff. This is due to the
fact that in the early and mid-twentieth century, the staff considered only as a resource for businesses, by which
objectives are achieved. But with the transition to a market economy in the beginning of the XXI century. When
many enterprises (organizations) were able to access to foreign markets and and cooperation with foreign
partners, the single most important competitive advantage of any enterprise (organization) becomes its human
resources– personnel who need to correct control.
The internationalization of the modern economy, the unprecedented increase in the number of contacts with
representatives of different countries and cultures, to improve their level of intensity, depth and diversity as well
as the degree of participation in international business initiated research in the field of personnel management
of the enterprise (organization) .Article is a comparative analysis of existing approaches Human Resources
Management and reveals the essence of cross-cultural approach to the management personnel of the enterprise
(organization) and showed its features. The article also presents characteristics of cross-cultural management
and especially its use.